Outpatient Platinum-Taxane Intraperitoneal Chemotherapy Regimen for Ovarian Cancer. Issue 7 (1st October 2009) - Seamon, Leigh G.; Carlson, Matthew J.; Richardson, Debra L.; Cohn, David E.; Fowler, Jeffrey M.; Copeland, Larry J.; O'Malley, David M.
Abstract : Introduction: Intraperitoneal (IP) chemotherapy is associated with an improved survival at the expense of increased toxicity in optimally debulked ovarian cancer patients. We describe the toxicity profile of an outpatient regimen of an intravenous (IV) and IP taxane-platinum chemotherapy. Methods: A chart review of all patients who received IP chemotherapy from December 2005 to May 2008 was performed. Optimally debulked patients after primary surgery for ovarian, primary peritoneal, or fallopian tubal cancer who received IV docetaxel 60 to 70 mg/m 2 and IP cisplatin 80 to 85 mg/m 2 on day 1 and IP paclitaxel 60 to 70 mg/m 2 on day 8 every 21 days were included. Toxicities were recorded using the Common Terminology Criteria for Adverse Events v3.0. Results: Thirty-three patients have completed chemotherapy. Of these, 19 patients (58%) completed all planned cycles of IP chemotherapy and 23 (70%) completed 75% or greater of the planned cycles. Four patients (12%) did not complete 50% or greater of the cycles. A total of 150.5 IP cycles were delivered, with a median number of 4 IP cycles (range, 0.5-7.5) completed. Grades 3 and 4 hematologic toxicities occurred in 21% of patients (n = 7), and 8 patients (24%) experienced grade 3 or 4 nonhematologic events. The overall response rate was 100% (complete response, 91%; partial response, 9.0%) with a progression-free survival of 19 months. Conclusions: This outpatient regimen of IV and IP platinum-taxane chemotherapy is well tolerated with acceptable toxicity. Importantly, most patients were able to complete all planned cycles of chemotherapy. These findings suggest that continued investigation of methods to decrease the toxicity of the treatment seen in the Gynecologic Oncology Group Protocol 172 is needed and should be studied in future phase 2 IP chemotherapy trials.